Digital Leadership of School Principals as a Key Driver of School Readiness in the Artificial Intelligence Era - Dismawati Dismawati; Disa Sri Ilma; Anton Anton; Yulius Efendi; Riska Meisyi Putri; Elfa Eriyani; Muhammad Ali Basroh (Al-Qalam Institue, 2026)
The rapid development of Artificial Intelligence (AI) has transformed educational systems and demands a high level of school readiness in terms of technology, organizational culture, and human resources. However, many schools remain inadequately prepared due to school leadership that has not fully adapted to digital transformation. This study aims to analyze how principals’ digital leadership influences school readiness in facing the AI era. Employing a qualitative approach, this research uses a systematic library research method by reviewing relevant scientific publications published between 2021 and 2026. The collected data were analyzed using thematic analysis to identify recurring patterns, key concepts, and dominant findings related to digital leadership and school readiness. The findings reveal that principals’ digital leadership plays a significant role in enhancing school readiness through three interconnected dimensions: the formulation of a strategic digital vision and effective management of digital infrastructure, the development of a supportive digital culture within the school environment, and the facilitation of continuous teacher professional development in response to AI-driven educational demands. These dimensions collectively contribute to the creation of an adaptive and sustainable school ecosystem. The study implies that principals must function as change agents who not only provide technological resources but also strategically strengthen institutional systems, organizational culture, and human resource capacities to ensure the effective and responsible implementation of AI in schools.